The Brazilian Legislation and the Recovering of Juvenile Offenders - Andreucci, Álvaro Gonçalves Antunes (2015)
This article treats of the historical background of Brazilian legislation concerning the punishment and rehabilitation of juvenile offenders. It begins with the psychological definition of what childhood and adolescence in relation to human development, and analyzes the existing legislation concerning the violation perpetrated by minors during the Brazilian legislative history. It shows that there is, on the one hand, a concern founded with the assistance to the lower, and the protection that is given to him in a vulnerable situation. It also presents which the gaps that prevent the effective recovery of minors in conflict with the law, criticizing, in the end, the simplistic policy of adopting the reduction of criminal responsibility as a way of reducing crime committed by persons below eighteen years.